2002
DOI: 10.1021/ja017681y
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning of Polymer Thin Films with pH-Sensitive and Cross-linkable Hydrogen-Bonded Polyelectrolyte Multilayers

Abstract: Polyelectrolyte multilayers of poly(acrylic acid) (PAA) and polyacrylamide (PAAm) were prepared via hydrogen-bonding interactions. These multilayers as assembled were stable at low pH but dissolved quickly in neutral pH water. We developed methods for stabilizing these multilayers to high pH through cross-linking by heating or UV-irradiation. Thermal treatment of the multilayers, which resulted in a partial imidization between carboxylic acid and amide groups, gave the multilayer good stability at high pH. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
353
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(363 citation statements)
references
References 11 publications
8
353
1
1
Order By: Relevance
“…Early attempts for selective multilayer assembly on specific areas involve microcontact printing through the use of self-assembled monolayers (SAMs) as molecular templates [69,70]. Later, non-lithographical means such as inkjet printing were introduced [71]. The development of new techniques, such as the ''lift-off'' approach [72], and the ''polymer on polymer'' stamping [73] were followed.…”
Section: Surface Patterningmentioning
confidence: 99%
“…Early attempts for selective multilayer assembly on specific areas involve microcontact printing through the use of self-assembled monolayers (SAMs) as molecular templates [69,70]. Later, non-lithographical means such as inkjet printing were introduced [71]. The development of new techniques, such as the ''lift-off'' approach [72], and the ''polymer on polymer'' stamping [73] were followed.…”
Section: Surface Patterningmentioning
confidence: 99%
“…As well-known, electrostatic interaction is the most common driving force to build self-assembly multilayer films [40]. Water-soluble and multiple charge are required for the components to construct the electrostatic LbL multilayers.…”
Section: Fabrication Of Multilayer Films Via Electrostatic Interactionmentioning
confidence: 99%
“…According to observations, the patterns are stable in aqueous solution and cell culture media for at least 5 weeks, with no apparent loss of fluorescence intensity, which agrees with other reports on the stability of multilayer nanofilms. 33,66,67 For observations performed up to 2 weeks in vitro, it was found that neurons preferentially bound to {PSS/PDDA} 3 /{sPLA 2 /(FITC-PEI) 4 }/sPLA 2 patterns compared with {PSS/ PDDA} 3 /{PSS/(TRITC-PLL)} 5 patterns. In addition, large and fine neuronal processes were observed, following preferential localization of cells on the FITC patterns.…”
Section: Cell Culturementioning
confidence: 99%